Zooming in and out of semantics: proximal–distal construal levels and prominence hierarchies - Lobben, Marit; Laeng, Bruno (Frontiers in Psychology, 2024)
We argue that the "Prominence Hierarchy" within linguistics can be subsumed under the "Construal Level Theory" within psychology and that a wide spectrum of grammatical phenomena, ranging from case assignment to number, definiteness, verbal agreement, voice, direct/inverse morphology, and syntactic word-order respond to Prominence Hierarchies (PH), or semantic scales. In fact, the field of prominence hierarchies, as expressed through the languages of the world, continues to be riddled with riddles. We identify a set of conundrums: A) vantage point and animacy, B) individuation and narrow reference phenomena, C) fronting mechanisms, D) abstraction, and E) cultural variance and flexibility. We here propose an account for the existence of these hierarchies and their pervasive effects on grammar by relying on psychological Construal Level Theory (CLT). We suggest that both PH and CLT structure the external world according to proximity or distance from the 'Me, Here and Now' (MHN) perspective. In language, MHN has the effect of structuring grammars; in cognition, it structures our lives, our preferences, and choices.